Editorial: Perspectivas y reflexiones desde las ciencias humanas (2020)
In this editorial, I will present eleven articles resulting from research or reflections from the perspectives and theoretical reviews of some topics of interest. The articles are authored by national and international professionals, who addressed among other topics, those related to the armed conflict in Colombia, colonial art, politics, education, values, consumerism and Gothic literature.